2011
DOI: 10.1097/ico.0b013e31821eeaad
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Central Macular Thickness After Uncomplicated Corneal Transplantation for Keratoconus: Penetrating Keratoplasty Versus Deep Anterior Lamellar Keratoplasty

Abstract: The study showed that DALK, although it is a closed-system technique, has a similar impact on the macula compared with PKP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Previous reports indicated that certain parameters such as age, race, refractive error, and axial length could affect OCT findings in the retina [22]. Although corneal irregularities present in KCN can compromise the optical quality of OCT retinal images, the technique can still reliably record retinal layer thicknesses in these patients [7,[23][24][25][26].…”
Section: Posterior Segment Evaluationmentioning
confidence: 99%
“…Previous reports indicated that certain parameters such as age, race, refractive error, and axial length could affect OCT findings in the retina [22]. Although corneal irregularities present in KCN can compromise the optical quality of OCT retinal images, the technique can still reliably record retinal layer thicknesses in these patients [7,[23][24][25][26].…”
Section: Posterior Segment Evaluationmentioning
confidence: 99%
“…The technique has the potential to reveal macular lesions due to various conditions and it is valuable for visualization of, for example, macular oedema. OCT has been shown to be able to measure retinal thickness despite the reduced optical quality of the cornea in KC subjects [ 12 14 ]; however, very little data is available to demonstrate if macular thickness is normal or unaffected by the disease. Therefore, the aim of this study was to compare the macular thickness in patients with KC with macular thickness in healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Although the postoperative 1st, 3rd and 6th month central macular thickness values were higher than the pre-operative values in both groups, but this increases was not statistically significant. The authors believed that the lack of a significant difference between the two groups although DALK was performed in a closed system were due to the fact that the big-bubble technique can disrupt the blood-retina barrier as much as PK and the long duration of DALK surgery (16).…”
Section: Resultsmentioning
confidence: 99%